Agreeing to arm: Bilateral weapons agreements and the global arms trade. (May 2016) - Kinne, Brandon J
This article assesses the impact of a new form of defense cooperation – formal weapons cooperation agreements, or WCAs – on the global arms trade. WCAs are bilateral framework agreements that establish comprehensive guidelines on the development, production, and exchange of conventional arms. Substantively, WCAs regulate such core areas as procurement and contracting, defense-based research and development, and defense industrial cooperation. These agreements have proliferated dramatically since the mid-1990s. They now number nearly 700, with 30–40 new WCAs signed each year. Newly collected data are used to analyze the effect of WCAs on import and export of conventional weapons. To control for interdependencies in the formation of WCAs, and to account for the mutually endogenous relationship between WCAs and weapons flows, WCAs are modeled as an interdependent network that coevolves with the individual-level arms trade activity of states. The analysis shows that, over the 1995–2010 period, WCAs have significantly increased weapons flows.